First Karyotypic Study of the Kissing Gouramies, Helostoma temminckii (Anabantiformes, Helostomatidae) from Thailand by Conventional and Ag-NOR staining techniques - Mingkwan, Boonyada; Chaiyachate, Rattanasuda; Tanomtong, Alongklod; Supiwong, Weerayuth (Food Agricultural Sciences and Technology, 2011)
The first chromosomal study of kissing Gouramies, Helostoma temminckii was karyotypically performed from Thailand. Kidney cells were obtained from ten of male and female specimens. Then, conventional staining and Ag-NOR banding were carried out to stain the chromosomes. The results of conventional staining mainly demonstrated telocentric chromosome with diploid number (2n) and fundamental number (NF) as 48. While, Ag-NOR banding technique presented the position of nucleolar organizer regions (NORs) at the end of telomere of chromosome pair four. Karyotype consisted of 16 large, 30 medium and two small telocentric chromosomes. Thus, the karyotype formula represented as follows: Lt16+Mt30+St2.